The Role Of Cosmetic Marketing Influencers On Online Purchase Decisions - Abel Khepemadaxa Sinukaban; Akbar Maulana; Feiziana; Nadra Valiza Shafira (PT. Altaf Publishing Corp, 2025)
In the cosmetics sector, influencer marketing has emerged as one of the most successful digital marketing techniques. The purpose of this study was to examine how influencer marketing influences consumers' decision to purchase cosmetics online. In a case study involving female college students aged between 19 and 25 who frequently use cosmetics, a qualitative research methodology was used. In-depth interviews were used to collect data, and triangulation techniques were used for analysis to ensure data validity. According to the findings, the main determinants of consumers' purchasing decisions are the quality of the original ingredients, their level of trust in the influencer, and how well the product meets their needs. The growth of consumer trust is further aided by the sincerity of the influencers in sharing good ratings and reviews from customers. This research will be of great help to cosmetic company owners who wish to use influencer marketing to create more successful marketing campaigns.